Proceedings of the International Conference of Mechatronics and Cyber-MixMechatronics - 2017 (Lecture Notes in Networks and Systems,, 2018)
This first edition of conference Proceedings reflects the expansion of the field of Mechatronics, which has now taken its place in the world of newer transdisciplinary fields of Adaptronics, Integronics, and Cyber-Mix Mechatronics. It presents state-of-the art advances in Mechatronics, Adaptronics, Integronics and Cyber-Mix-Mechatronics. The 1st International Conference of Mechatronics and Cyber-MixMechatronics/ICOMECYME was organized by the National Institute of R&D in Mechatronics and Measurement Technique in Bucharest (Romania), on September 7th-8th, 2017 and attracted specialists from all over the world-including North America, South America, and Asia. In addition to presenting research results, ICOMECYME also offered a forum for exchange between R&D experts. .